Raja-raja Mataram Kuna dari Sanjaya Sampai Balitung Sebuah Rekonstruksi Berdasarkan Prasasti Wanua Tengah III - nfn. Kusen (Balai Arkeologi Yogyakarta, 1994)
This article re-presents the historical data contained in the Wanua Tengah Ill inscription, especially regarding the ancient Mataram kings. The data had been neglected by the editorial team in the writing of the Sejarah Nasional Indonesia II. The historical reconstruction of kings, especially from Sanjaya to Balitung, shows how valuable the historical data in Wanua Tengah Ill inscription. It is hoped that the contents of article will become one of the considerations in rewriting ancient Mataram kings in the future.